(3ebGeGJ GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3YHO GdefYe Hf GdMGL LeYI GdMhGhTj s)
(3ChdgG (B:s
(3ef ebGeI QTa GdRdGd , bhdg (B: (3bGd GdTjN GdEeGe Mci CHhGdOQ fajS GHf CHj EOQjS s
(3BNQgG (B:s
(3ef GdebGeI GdjGbhJjI, bhdg acCfg bVH GdRHQLO NVQ bO beYhG CWQGag ajQhRLG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B209-236 - (3U(B224-278s
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3YOJgG SHY ebGeGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs